PENGARUH NET OPERATING MARGIN (NOM) DAN FINANCING TO DEPOSIT RATIO (FDR) TERHADAP CAPITAL ADEQUACY RATIO (CAR) PADA BANK UMUM SYARIAH DI INDONESIA - Annisa Fitriana, Ika; Fatmawatie, Naning; Mutafarida, Binti (Islamic Economics Program, Faculty of Islamic Economics and Business, 2024)
This research employs a quantitative method with a caisal-comparative design. The population for this study consists of Sharia Commercial Banks registered with the Financial Services Authority, selected through purposive sampling criteria determined by the researcher. The 2018-2022 period was chosen because it represents the most recent years, during which the global economy was impacted by the negative effects of the Covid-19 pandemic. This period saw a weakening of the banking system, particularly affecting Islamic banks in Indonesia. Based on the established criteria, there are 9 Sharia Commercial Banks that meet the researcher’s criteria. The total sample size for this study is 45 data points. The results of the study indicate that, in partial testing Net Operating Margin has an influence on Capital Adequacy Ratio, while Financing To Deposit Ratio does not have an influence Capital Adeqyacy Ratio. Net Operating Margin and Financing To Deposit Ratio collectively contrubute to 23,3% of the influence on Capital Adequacy Ratio, with the remaining 76,7% influenced by variables outside the scope of this study.